2022
DOI: 10.33584/jnzg.2021.83.3497
|View full text |Cite
|
Sign up to set email alerts
|

The effect of winter fodder beet or kale allocation on behaviour and blood metabolite status of non-lactating dairy cows

Abstract: Fodder beet (FB) was at first rapidly adopted by farmers, however, there is uncertainty around the impact of feeding high rates of FB on metabolic diseases and cow behaviour. This study aimed to establish if there was an effect of crop type and feed allocation on blood metabolites and behaviour of dairy cows. In winter 2017, 328 mixed-aged pregnant non-lactating Friesian x Jersey cows were allocated to feeding treatments of either FB or kale, offered at two allocation rates: “target” (to achieve 0.5 BCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Quality results indicated that FB had lower levels of P, S, Ca and NDF than kale, in agreement with findings from Dalley et al (2020a). Phosphorus levels in FB were numerically lower than the recommended levels over winter (NASEM 2021) which is similar to previous findings (Dalley et al 2021). These observations reinforce the need for P supplementation when feeding FB to pregnant, nonlactating cows over winter.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Quality results indicated that FB had lower levels of P, S, Ca and NDF than kale, in agreement with findings from Dalley et al (2020a). Phosphorus levels in FB were numerically lower than the recommended levels over winter (NASEM 2021) which is similar to previous findings (Dalley et al 2021). These observations reinforce the need for P supplementation when feeding FB to pregnant, nonlactating cows over winter.…”
Section: Discussionsupporting
confidence: 87%
“…Nutritional deficiencies associated with kale feeding are less common. However, Dalley et al (2021) has reported that cows wintered on a kale diet had lower blood Ca than cows on FB. Research at the Southern Dairy Hub (SDH) also reported blood magnesium (Mg) levels in the lower end (0.75-0.8 mmol/l) of the normal range in cows grazing kale (Dalley 2018;Dalley et al 2021).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations